2005
DOI: 10.1111/j.1601-5037.2004.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

A study in vitro of the combined effects of soft drinks and tooth brushing with fluoride toothpaste on the wear of dentine

Abstract: The aim of this study was to measure loss of dentine produced by soft drinks alone and combined with tooth brushing with and without toothpastes. Groups of flat human dentine specimens were exposed for 10 min and then 30 min to orange juice (OJ), carbonated cola (CC) or modified blackcurrant (MB) drinks alone or after the exposures brushed with a fluoride toothpaste for 10 s. Further groups were exposed to OJ as before but brushed with water or non-fluoride toothpaste or placed in slurries of fluoride paste. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 29 publications
5
38
1
7
Order By: Relevance
“…Rios et al (22) stated that even some kinds of toothpastes accelerate tooth wear due to the removal of superficial enamel layer. Ponduri et al (23) reported that non-fluoride toothpaste could increase dentine loss compared with drinks alone. On the contrary; fluoride and re-mineralizing toothpastes (containing NaF, calcium, phosphate, and fluoride ions) are effective in inhibiting enamel erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Rios et al (22) stated that even some kinds of toothpastes accelerate tooth wear due to the removal of superficial enamel layer. Ponduri et al (23) reported that non-fluoride toothpaste could increase dentine loss compared with drinks alone. On the contrary; fluoride and re-mineralizing toothpastes (containing NaF, calcium, phosphate, and fluoride ions) are effective in inhibiting enamel erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Non-fluoride toothpaste could increase dentine loss compared with drinks alone (Ponduri et al, 2005). Whitening dentifrice also leads to significantly greater wear of sound enamel and of both eroded and sound dentine (Turssi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…44 However, the incorporation of new hydroxyapatite into demineralized enamel is 30% reduction in wear when compared with a placebo). 26,27 Based on these findings, highly concentrated fluoride dentifrices (5000 ppm F, NaF) have been tested, but the results obtained so far are inconclusive. In an in situ study, a commercial dentifrice with 5000 ppm F had the same positive effect as another commercial 1100 ppm F dentifrice (NaF) on eroded and eroded-abraded dentin.…”
mentioning
confidence: 99%